2014
DOI: 10.1163/15685403-00003316
|View full text |Cite
|
Sign up to set email alerts
|

Environmental driving forces determining the epipelagic decapod larval community distribution in the Balearic Sea (western Mediterranean)

Abstract: The decapod larvae community inhabiting the Balearic Sea surface waters was studied from plankton surveys carried out in the spring and summer of 2004 and 2005 between 38°N 0.5°E and 42°N 6°E. A total of 84 taxa were identified, from seven taxonomic orders. The mean larval densities varied from 0.01-240 (±11.69) individuals 100 m−3in 2004 to 0.40-600 (±26.89) individuals 100 m−3in 2005. The analysis of larval spatial patterns in relation to the observed inter-annual environmental variability indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…to 2,300 m). Similar assemblage analyses were restricted in the BSB to the epipelagic (0–200 m) of the water column (Carbonell et al., 2014), so the present study is somehow completing what happens in the meso (at the deep scattering layer, DSL) and bathypelagic near the seafloor (the benthic boundary layer, BBL). We identified different assemblages (regarding their composition and abundance) in the mainland and insular areas and at different layers of the water column (DSL and BBL).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…to 2,300 m). Similar assemblage analyses were restricted in the BSB to the epipelagic (0–200 m) of the water column (Carbonell et al., 2014), so the present study is somehow completing what happens in the meso (at the deep scattering layer, DSL) and bathypelagic near the seafloor (the benthic boundary layer, BBL). We identified different assemblages (regarding their composition and abundance) in the mainland and insular areas and at different layers of the water column (DSL and BBL).…”
Section: Discussionsupporting
confidence: 62%
“…Yet, larvae assemblages in deep waters remain virtually unknown. The available studies showed a limited larval dispersal capacity and larvae distribution in patches, suggesting that hydrography drivers model larval distribution (Rodríguez et al, 2013; Carbonell et al., 2014). Given the opportunity to explore these environmental and hydrographic conditions in deep, the present study analyses the decapod larvae spatial distribution and composition in the deep BSB and discusses the potential oceanographic modeling connectivity and dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Also near the continental slope, a cascading of colder and even denser water was found , affecting biological processes over the whole water column (e.g. Company et al, 2008;Rodríguez et al, 2013;Carbonell et al, 2014;Hidalgo et al, 2014). In the last years, linked to the growing interest in Mediterranean Sea health state, new variables (pH, Total Inorganic Carbon, NO 2 , CH 4 ) have been added to the original sampling (Amengual et al, 2010).…”
Section: Hydrographic Monitoring Sectionsmentioning
confidence: 99%
“…Company et al, 2008;Guijarro, 2012;Rodríguez et al, 2013;Carbonell et al, 2014;Hidalgo et al, 2014), and therefore the marine resources and their exploitation.…”
Section: Radmed Scientific Motivationsmentioning
confidence: 99%